Hyperfine induced transition probabilities from 4f145s5p3P0, 2o states in Sm-like ions. (23rd October 2017) - Zhou, Fuyang; Li, Jiguang; Qu, Yizhi; Wang, Jianguo
Abstract: The hyperfine induced 4 f 14 5 s 5 p 3 P 0, 2 o − 4 f 14 5 s 2 1 S 0 transition probabilities for highly charged Sm-like ions are calculated within the framework of the multiconfiguration Dirac–Hartree–Fock method. Electron correlation, the Breit interaction and quantum electrodynamical effects are taken into account. For ions ranging from Z = 79 to Z = 94, 4 f 14 5 s 5 p 3 P 0 o is the first excited state, and the hyperfine induced transition (HIT) is a dominant decay channel. For the 4 f 14 5 s 5 p 3 P 2 o state, the HIT rates of Sm-like ions with Z = 82 − 94 are reported as well as the magnetic dipole (M1) 3 P 2 o − 3 P 1 o, the electric quadrupole (E2) 3 P 2 o − 3 P 0, 1 o, and the magnetic quadrupole (M2) 3 P 2 o − 1 S 0 transition probabilities. It is found that M1 transition from the 4 f 14 5 s 5 p 3 P 2 o state is the most important decay channel in this range on Z ≥ 82 .